Estado, mercado e a produção imobiliária residencial de São Paulo, 2014-2018 - Silva, Hugo Louro e (2020)
This work involves from the Brazilian economic matrix and the vertical residential real estate production developed by the private initiative in the city of São Paulo, between the years 2014 and 2018. 2014 was a year that marked the beginning of a period of crisis and economic changes in the Brazilian scenario; and, also, the approval of the new Strategic Master Plan for 2014 (PDE-2014). We point out that the process of changing the residential profile of urban production, promoted by the private sector in São Paulo, took place through a conjuncture between the economic scenario, the regulations in the federal sphere - by reaffirming the economic matrix of support for the production of available housing in force in Brazil, including the Programa Minha Casa, Minha Vida – and at the municipal level – through the PDE-2014, the Land Installment, Use and Occupation Law of 2016 (LPUOS-2016), the “HIS Law” of 2016 and the Works and Buildings Code of 2017 (COE-2017 ). When confronting the systematized empirical data with the theoretical framework raised, observing the economic context, and the participation of the State, at the federal level – through the Caixa Economica Federal and the Programa Minha Casa, Minha Vida – and, still, the regulatory marks in municipal sphere - which intended to redirect the profile of urban real estate production generated by the private initiative, to a more compact city with social housing - we present in this work the structural and conjunctural components that, concatenated, allowed the change in the profile of vertical urban residential real estate production, within an economic and regulatory framework.